Health-Predictive Social-Environmental Stressors and Social Buffers Are Place Based: A Multilevel Example From San Bernardino Communities - Kristen N. Arthur; Synnøve F. Knutsen; Rhonda Spencer-Hwang; David Shavlik; Susanne Montgomery (SAGE Publishing, 2019)
Significant evidence demonstrates the powerful effects social determinants have on health-related perceptions, behaviors, and health outcomes. However, these factors are often studied out of context, despite the acknowledgement that social determinants of health are place based. This research aimed to demonstrate that health-related perceptions are dependent on where one lives. Via a community-based participatory study, participants were randomly selected from 3 residential regions varying distances from a freight railyard (nearest n = 300, middle n = 338, farthest n = 327), all mostly low-income, predominately Latino areas. Interview-administered surveys with adults were collected by bilingual trained community members (87% response) in English/Spanish. Adjusted-logistic regression models assessed residential region as a predictor of stressors (perceptions of community safety, community noise disturbance, health care access, food insecurity) and buffers (3 neighborhood cohesion variables), after adjusting for household income, race/ethnicity, gender, and age. Each region experienced a unique amalgam of stressors and buffers. In general, the region closest to the railyard experienced more stressors (odds ratio [OR] = 1.58; 95% CI 1.12-2.20) and less buffers (OR = 0.69; 95% CI 0.49-0.96) than the region furthest from the railyard. More than half of participants in each region reported 2 or more stressors and 2 or more buffers. In this seemingly homogenous study population, place remained important in spite of traditionally used socioeconomic factors, such as household income and race/ethnicity. Social determinants of health should be studied with regard to their environmental context, which will require interdisciplinary collaboration to improve multilevel research methods. Including the study of social buffers will also promote sustainable, positive change to reduce health disparities.